The influence of stressor on blood pressure in school children - Sudung O Pardede; Partini P Trihono; Irene Yuniar; Taralan Tambunan (Indonesian Pediatric Society, 2003)
Background Physical and psychological stress such as child anxi-ety, can increase blood pressure.Objective To evaluate the role of vein puncture as a stressor caus-ing alteration of blood pressure in school children.Methods This study was a descriptive, pre and post test study asa part of a screening study on primary school children at Cibubursubdistrict in East Jakarta. Blood pressure was measured beforeand after a vein puncture procedure in 449 children. Nine childrenwere excluded because of incomplete data.Results The increase of systolic blood pressure was found in 121(27.5%) subjects, decrease in 42 (9.5%), and no change in 227(63%). Diastolic blood pressure increased in 123 (28.0%) subjects,decreased in 38 (8.6%), and did not change in 279 (63.4%). Theincrease of both systolic and diastolic blood pressure was found in61 (13.8%), increased systolic with no change of diastolic in 58(13.2%), and increased systolic with decreased diastolic in 2 (0.5%)children. Decreased systolic with increased diastolic was found in2 (0.5%) subjects, decreased systolic with no change of diastolicin 26 (5.9%), and decrease of both systolic and diastolic in 14 (3.2%)children. No changes in both systolic and diastolic blood pressurewere found in 195 (44.3%); no change in systolic with decreaseddiastolic blood pressure was found in 22 (5.0%) children.Conclusion In most of the school children, vein puncture proce-dure did not cause alteration on blood pressure